Liturgy of Empire: Reading the Mozarabic Rite in Early Modern Europe, 1500-1800 - Boynton, Susan Leslie (Early Modern History and Modern History E-Books Online, Collection 2025., 2026)
Liturgy of Empire examines the European reception of the neo-Mozarabic rite created under the patronage of the Archbishop of Toledo, Francisco Jimenez de Cisneros (1495-1517), in relation to the history of the Mozarabs of Toledo, the development of bibliophilia and libraries, the scholarly study of medieval liturgy, and the crusading ideology of Spanish expansionism in the Mediterranean. During the emergence of Spain's global empire, the editions of the Mozarabic rite entered collections throughout Europe. The provenance of the copies (studied here for the first time) reveals their mediation of knowledge about Iberian history and the political contexts for their acquisition.